Anisotropic Panglial Coupling Reflects Tonotopic Organization in the Inferior Colliculus - Wadle, Simon L.; Augustin, Vanessa; Langer, Julia; Jabs, Ronald; Philippot, Camille; Weingarten, Dennis J.; Rose, Christine R.; Steinhäuser, Christian; Stephan, Jonathan (Frontiers in Cellular Neuroscience, 2018)
Astrocytes and oligodendrocytes in different brain regions form panglial networks and the topography of such networks can correlate with neuronal topography and function. Astrocyte-oligodendrocyte networks in the lateral superior olive (LSO) – an auditory brainstem nucleus – were found to be anisotropic with a preferred orientation orthogonally to the tonotopic axis. We hypothesized that such a specialization might be present in other tonotopically organized brainstem nuclei, too. Thus, we analyzed gap junctional coupling in the center of the inferior colliculus (IC) – another nucleus of the auditory brainstem that exhibits tonotopic organization. In acute brainstem slices obtained from mice, IC networks were traced employing whole-cell patch-clamp recordings of single sulforhodamine (SR) 101-identified astrocytes and concomitant intracellular loading of the gap junction-permeable tracer neurobiotin. The majority of dye-coupled networks exhibited an oval topography, which was preferentially oriented orthogonal to the tonotopic axis. Astrocyte processes showed preferentially the same orientation indicating a correlation between astrocyte and network topography. In addition to SR101-positive astrocytes, IC networks contained oligodendrocytes. Using Na+ imaging, we analyzed the capability of IC networks to redistribute small ions. Na+ bi-directionally diffused between SR101-positive astrocytes and SR101-negative cells – presumably oligodendrocytes – showing the functionality of IC networks. Taken together, our results demonstrate that IC astrocytes and IC oligodendrocytes form functional anisotropic panglial networks that are preferentially oriented orthogonal to the tonotopic axis. Thus, our data indicate that the topographic specialization of glial networks seen in IC and LSO might be a general feature of tonotopically organized auditory brainstem nuclei.